A Case Study of Communication Skills Implementation: The Effective Communication of School Teachers during the Covid-19 Pandemic - Edi Sumarwan; Rapiadi Rapiadi; Iin Avitasari; Sidartha Adi Gautama; Wistina Seneru (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
This study analyzes effective communication in Buddhist Religious Education (BRE) learning during the Covid-19 pandemic at Bandar Agung Elementary School 4, Bandar Sribhawono Subdistrict. The study utilizes a qualitative approach and a case study method. Data is collected through observation, interviews, and documentation, which are then analyzed using the Miles and Huberman data analysis model. The research findings indicate that teachers use WhatsApp and video calls as communication channels for distance learning. Teachers also involve parents or family members of the students as communication intermediaries. Interactive teaching methods such as questioning, discussions, and lectures are employed. The study also identifies communication barriers such as limited internet access and technological proficiency. Teachers address these barriers by directly communicating with students and parents through home visits. This research highlights the importance of effective communication in BRE learning during the Covid-19 pandemic and the strategies used to overcome communication challenges.